Cook-Ed(TM): A Model for Planning, Implementing and Evaluating Cooking Programs to Improve Diet and Health - Asher, Roberta C. (Nutrients, 2020)
Domestic cooking education programs are typically designed to improve an individual’s food and cooking skills, although not necessarily diet quality. Currently, there are no comprehensive models to guide the planning, implementation and evaluation of domestic cooking education programs that focus on improving diet and health. Our aim was to address this through development of the Cooking Education (“Cook-Ed(TM)”) model, using the PRECEDE-PROCEED model as the underlying Cook-Ed(TM) framework. A review of the food and cooking skills education literature informed the content of the Cook-Ed(TM) model. Cook-Ed(TM) was critiqued by experts in consumer behaviour, cooking and nutrition education research and education until consensus on model content and format was reached. Cook-Ed(TM) leads cooking program developers through eight distinct stages, engaging key stakeholders in a co-design process from the outset to tailor programs to address the need of individuals and inform the development of program content, program delivery, and evaluation. A Cook-Ed(TM) scenario applied in practice is described. The proposed Cook-Ed(TM) model has potential to be adapted for use in domestic cooking education programs delivered in clinical, community, school or research settings. Further research will establish Cook-Ed(TM)’s utility in enhancing program development and in improving food and cooking skills, dietary patterns and health outcomes.